Serotonergic antidepressants as predictors of depressive disorders treatment - Timotijević Ivana P.; Todorović Mirjana M.; Crnić Katarina B.; Marković Srđan Z.; Kastratović Dragana A. (Srpsko lekarsko drustvo, 2014)
From Kraepelin time to these days, biochemical, neurophysiological and neuropsychological complexity of depression has been reviewed in many different ways, but SSRI antidepressants have unquestionably brought about a significant drift in comprehension of disease, recognition of symptoms, and management. The fact is that high tech and accurate molecular studies may differentiate biological basis (receptor activity, transmitter concentrations not only in synapses, but also in particular CNS structures, cascade processes to changes of genomes in postsynaptic neurons) of some depression symptoms. It is a significant progress in overview of psychiatric disorders because any symptom has its equivalent in CNS processes as antidepressants have their recognizable mechanisms of action. In this dynamic drug/disease relation, standard psychiatric classifications maintain their significance yet their approach remains descriptive what is no longer enough for selection of psychopharmacotherapy. Abandonment of categorical and adoption of dimensional approach means that any individual patient has his individual symptom portfolio created and that every symptom is hypothetically mapped in appropriate CNS structures and corresponding impaired information processes, dependent upon neurotransmitter pathways within these structures and connecting neuronal networks. Such approach opens up a possibility for combination of psychopharmacological drugs in different psychiatric categories what will be a huge benefit for patients, because targeted psychopharmacotherapy adjusts therapeutical effect and reduces the number of side effects and intolerable interactions. SSRI antidepressants, due to their broad spectrum of pharmacological characteristics and multiple psychiatric indications may be predictors of diagnostic categorization, causal psychopharmacotherapy and path to further research of etiopathogenesis of affective disorders.